1955
DOI: 10.3733/hilg.v24n04p069
|View full text |Cite
|
Sign up to set email alerts
|

Reclamation of a saline and high boron soil in the Coachella Valley of California

Abstract: With the expansion of irrigated agriculture throughout the world, much land now saline or alkaline must be reclaimed. Reported herein are the results of both flushing and leaching salts from a saline-alkali soil in the Coachella Valley of California's Colorado Desert. The paper presents a quantitative evaluation of the effectiveness of removing a salt crust by flushing, and it compares the removal of the usual salts with the re moval of a high concentration of boron. Flushing as a reclamation procedure was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
4

Year Published

1958
1958
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 4 publications
0
11
0
4
Order By: Relevance
“…Segundo Rhoades & Loveday (1990) embora tenham sido desenvolvidos modelos determinísticos para simular a recuperação de solos salinos, as estimativas da quantidade de água de lixiviação necessária são baseadas em relações empíricas, derivadas de pesquisas e experiências de campo. Exemplos destes modelos são aqueles desenvolvidos por Reeve et al (1955), van der Molen (1956) e diversos outros modelos apresentados por FAO (1973).…”
Section: Introductionunclassified
“…Segundo Rhoades & Loveday (1990) embora tenham sido desenvolvidos modelos determinísticos para simular a recuperação de solos salinos, as estimativas da quantidade de água de lixiviação necessária são baseadas em relações empíricas, derivadas de pesquisas e experiências de campo. Exemplos destes modelos são aqueles desenvolvidos por Reeve et al (1955), van der Molen (1956) e diversos outros modelos apresentados por FAO (1973).…”
Section: Introductionunclassified
“…However, this concept has been strongly challenged by some investigators (Bowen 1968(Bowen , 1969(Bowen , 1972,Bowen and Nissen 1977;Reisenauer et al 1973 (Wolf 1940;Eaton 1944;Dible and Berger 1952 (L.) Merr.) Ieaves contained the most B (52-100 pg'g-'), the growing tip was next (28-59 pg'g-') and stems contained the least (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) Fg'g-').…”
Section: Sources Of Boron In the Environmentmentioning
confidence: 99%
“…Leaching experiments Reeve et al, 1955;Rhoades et al, 1970b) showed that a large fraction of soil boron can be removed by percolating waters but that the remainder persists even after large amounts of water have been applied.…”
Section: A Dynamics Of Boron Release From Soil Constituentsmentioning
confidence: 99%